Multifunctional Activities of Gold Nanoparticles Biosynthesized Using Bacteria Isolated from Mining Areas - Chih-Yu Chen; Yung-Chu Chang; Teh-Hua Tsai; Man-Hai Liu; Ying-Chien Chung (Applied Sciences, 2021)
Research on gold nanoparticles (AuNPs) has often focused on their physical, chemical, and crystalline characteristics. Commercial AuNPs have been applied in the diverse fields of biomedicine, catalysis, photovoltaics, and sensing. In this study, we explored the various activities of AuNPs to widen their applicability. This paper presents a simple and rapid synthesis process of AuNPs with bacteria isolated from a gold mining area. We also investigated the optimization of reaction parameters for AuNP synthesis. The study results revealed that among the isolated strains, Bifidobacterium lactis and Escherichia coli demonstrated the highest capabilities of AuNP synthesis. The optimal pH values for AuNP synthesis by B. lactis (BLAuNPs) and E. coli (ECAuNPs) were 5.0 for 72 h of incubation and 8.0 for 24 h of incubation. The average particle sizes of ECAuNPs and BLAuNPs were 4.2 and 5.6 nm, respectively. Furthermore, these biogenic AuNPs were found to be stable with no aggregation after 3 months of storage. BLAuNPs and ECAuNPs exhibited high levels of antimicrobial, antioxidant, photocatalytic, and antityrosinase activity. Moreover, they were noncytotoxic to skin cells even at 100% melanin inhibitory concentrations. Considering the demonstrated multifunctional activities of AuNPs, BLAuNPs and ECAuNPs have promising potential for commercialization.